Advances in cabohydrate chemistry and biochemistry - Horton, Derek (San Diego ; London ; New-York : Academic Press, 1997)
Since its inception in 1945, this serial has provided critical and integrating articles written by research specialists in industrial, analytical, and technological aspects of biochemistry, organic chemistry, and instrumentation methodology in the study of carbohydrates. The articles provide a definitive interpretation of the current status and future trends in carbohydrate chemistry and biochemistry.
Includes bibliographical references and indexes.
Keywords: Carbohydrates